South Asia in Transition: Strategic Landscape and Regional Order - Mazhar Jamil (CISS Insight Journal, 2025)
The strategic landscape of South Asia is largely defined by the balance of power dynamics between two nuclear-weapon states, i.e., India and Pakistan. The historically contentious relationship between India and its neighboring states also influences the security dynamics of this region. Instead of focusing on peace through cooperative frameworks, South Asia often contends with a zero-sum security approach. Alongside, India’s ambitions for regional hegemony and its aspirations for a great power status have further undermined the stability of this region. Under the current leadership of the Bharatiya Janata Party (BJP), the emergence of a Hindutva-inspired ideology, along with the conceptualization of Bharat as a Hindu Rashtra, has significantly transformed the security landscape of South Asia, thereby making it more complex and volatile. India’s ideological shifts, accompanied by a revisionist historical narrative, coupled with a false sense of conventional superiority and hegemony, have begun to undermine regional peace and stability in an unprecedented way. This paper aims to assess how India’s evolving strategic thought is influencing the regional security environment, peace, and stability. Additionally, the paper explores how Pakistan can respond to these developments as a responsible nuclear-weapon state. It also offers possible avenues for mutual strategic restraint to maintain peace and stability in the region.